2020
DOI: 10.18632/aging.103424
|View full text |Cite
|
Sign up to set email alerts
|

Altered circular RNA expression profiles in the non-ischemic thalamus in focal cortical infarction mice

Abstract: Focal cerebral infarction leads to secondary changes in non-ischemic areas remote from but connected to the infarct site. Circular RNAs (circRNAs) are involved in the pathophysiological processes of many diseases. However, the expression and roles of circRNAs in non-ischemic remote regions after ischemic stroke remain unknown. In this study, adult male C57BL/6J mice were subjected to permanent distal middle cerebral artery occlusion (MCAO) to establish focal cortical infarction. High-throughput sequencing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…CircRNAs, which are made up of introns or exons and formed through gene rearrangement or non-linear mode of RNA splicing, are widely present in the human cell [ 18 , 19 ]. They are more stable and more conserved compared with the other noncoding RNAs, which lead to potentially be used as new diagnostic molecular biological markers and therapeutic targets [ 20 , 21 ]. Recently, many studies had shown that circRNAs exert the regulation functions in multiple diseases, such as cardiovascular disease [ 22 ], lung cancer [ 23 ], Alzheimer’s disease [ 24 ], and neurological disorders [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs, which are made up of introns or exons and formed through gene rearrangement or non-linear mode of RNA splicing, are widely present in the human cell [ 18 , 19 ]. They are more stable and more conserved compared with the other noncoding RNAs, which lead to potentially be used as new diagnostic molecular biological markers and therapeutic targets [ 20 , 21 ]. Recently, many studies had shown that circRNAs exert the regulation functions in multiple diseases, such as cardiovascular disease [ 22 ], lung cancer [ 23 ], Alzheimer’s disease [ 24 ], and neurological disorders [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duan and coworkers conducted high-throughput sequencing of whole-brain tissues on the infarcted side 4 days after MCAO in rats [ 47 ]. Li et al [ 48 ] analyzed circRNAs in thalamic tissues on the infarcted side 7 and 14 days after focal cerebral infarction in mice, and the Mehta group used microarrays to detect changes in whole-brain circRNA expression patterns at 6, 12, and 24 h after post-MCAO reperfusion in mice [ 49 ]. Wouters and colleagues demonstrated a clear correlation between stroke severity in the early stages, especially at 24 h of onset, and stroke recovery [ 50 ], and they validated the importance of early stroke injury changes and interventions for stroke management [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it was found that circBBS2 and circPHKA2 were differentially expressed in the blood of AIS patients. Li et al found that a total of 2 659 circRNAs were significantly altered in the ipsilateral thalamus of adult male C57BL/6J mice in the permanent distal MCAO model compared with the sham-operated group (154). Among them, 73 circRNAs were significantly changed at 2 time points after modeling (154).…”
Section: Mehta Et Al Established a Tmcao Model In Male C57bl6jmentioning
confidence: 99%
“…Li et al found that a total of 2 659 circRNAs were significantly altered in the ipsilateral thalamus of adult male C57BL/6J mice in the permanent distal MCAO model compared with the sham-operated group (154). Among them, 73 circRNAs were significantly changed at 2 time points after modeling (154). GO and KEGG analysis showed that circRNAs play an important role in secondary thalamic neurodegeneration and remodeling after focal cortical infarction, suggesting that circRNAs may be therapeutic targets to alleviate secondary distal neurodegeneration after stroke.…”
Section: Mehta Et Al Established a Tmcao Model In Male C57bl6jmentioning
confidence: 99%